Cell-autonomous role of endothelial GTP cyclohydrolase 1 and tetrahydrobiopterin in blood pressure regulation - Chuaiphichai, S; McNeill, E; Douglas, G; Crabtree, M; Bendall, J; Hale, AB; Alp, N; Channon, K (Lippincott Williams and Wilkins, 2014)
Tetrahydrobiopterin (BH4) is an essential cofactor for endothelial nitric oxide synthase (eNOS) function and NO generation. Augmentation of BH4 levels can prevent eNOS uncoupling and can improve endothelial dysfunction in vascular disease states. However, the physiological requirement for de novo endothelial cell BH4 biosynthesis in eNOS function remains unclear. We generated a novel mouse model with endothelial cell-specific deletion of GCH1, encoding GTP cyclohydrolase 1, an essential enzyme for BH4 biosynthesis, to test the cell-autonomous requirement for endothelial BH4 biosynthesis in vivo. Mice with a floxed GCH1 allele (GCH1fl/fl) were crossed with Tie2cre mice to delete GCH1 in endothelial cells. GCH1fl/flTie2cre mice demonstrated virtually absent endothelial NO bioactivity and significantly greater O 2 •- production. GCH1fl/flTie2cre aortas and mesenteric arteries had enhanced vasoconstriction to phenylephrine and impaired endothelium-dependent vasodilatations to acetylcholine and SLIGRL. Endothelium-dependent vasodilatations in GCH1fl/fl Tie2cre aortas were, in part, mediated by eNOS-derived hydrogen peroxide (H2O 2), which mediated vasodilatation through soluble guanylate cyclase. Ex vivo supplementation of aortic rings with the BH4 analogue sepiapterin restored normal endothelial function and abolished eNOS-derived H 2O2 production in GCH1fl/flTie2cre aortas. GCH1fl/flTie2cre mice had higher systemic blood pressure than wild-type littermates, which was normalized by NOS inhibitor, N G-nitro-L-arginine methyl ester. Taken together, these studies reveal an endothelial cell-autonomous requirement for GCH1 and BH4 in regulation of vascular tone and blood pressure and identify endothelial cell BH4 as a pivotal regulator of NO versus H2O2 as alternative eNOS-derived endothelial-derived relaxing factors. © 2014 American Heart Association, Inc.